Effect of diclofenac and nimesulide on haematology in dogs - RAMESH, N; JAYAKUMAR, K; HONNEGOWDA, HONNEGOWDA; NARAYANA, K (The Indian Journal of Animal Sciences, 2014)
Diclofenac sodium and nimesulide were given @ 3 mg/kg twice daily for 4 days and 2 mg/kg twice daily for 4 days, respectively, orally to dogs (n=4). Among the different haematological parameters assessed, Hb, PCY, TLC and DLC values did not differ significantly when compared with the control group. Although the TEC values in both the diclofenac and nimesulide groups decreased during the course of experiment, the decrease was significant only in the nimesulide group at 96 hr. Hence, the 2 drugs in general did not affect the haematological parameters in dogs.